A apreciação de uma mulher: uma tradução comentada de Anne Gilchrist and Walt Whitman, de Elizabeth Porter Gould - Canto, Daniela Schwarcke do (2020)
Anne Gilchrist was a writer, biographer and translator. At the age of thirty-three, a widow and mother of four, she became well-known in the London literary scene when she finished The Life of William Blake (1863), a work left unfinished by her husband, the also writer Alexander Gilchrist, when he died. A few years later, another literarian benefits from Anne's talents, only this time from across the ocean. The American poet, Walt Whitman, who was at the time going through a difficult period in his literary career, is fortunate to find in this woman an unprecedented friend and admirer, who writes an inspired review of his Leaves of Grass (1855), helping change the negative impression some people had of both the poet and his work. This doctoral dissertation aims to introduce the talented Anne Gilchrist to the Portuguese-speaking public through the translation of Elizabeth Porter Gould’s Anne Gilchrist and Walt Whitman, published in 1900, which covers the period Anne spent in the United States in Whitman’s company. This dissertation is divided into four chapters: chapter one brings a brief biography of Anne Gilchrist; chapter two presents a concise analysis of biography as a literary genre; chapter three concerns the importance of language and culture and the role of the translator; and the fourth and last chapter consists of the translation of Gould's biography with comments on the translation strategies.